The fall and rise of experiential construction and engineering education: decoupling and recoupling practice and theory. Issue 1 (1st January 2017) - Forster, Alan Mark; Pilcher, Nick; Tennant, Stuart; Murray, Mike; Craig, Nigel; Copping, Alex
Abstract: From the mid-20 th C., construction and engineering pedagogy and curricula have moved from long-held traditional experiential apprenticeship approaches to one ostensibly decoupling practice and theory. This paper traces this decoupling and explores modern-day opportunities and challenges for recoupling university education with industry practice. Within this context the UK Government funds Graduate Level Apprenticeships (GLA) and introduces the Teaching Excellence Framework (TEF), arguably signalling a desire to recouple. Nevertheless, many challenges from following previous UK Government policy prioritising research remain, particularly for post-1992 institutions. Arguably, Higher Education Institutions (HEI's) are at a pedagogical crossroads, considering whether to choose REF-ville, TEF-ville, and/or Apprentice Township. Do HEI's continue their increasingly decontextualized theoretical approach, or re-embrace construction and engineering education's experiential roots? We present and discuss opportunities and challenges currently facing HEI's, aiming to help inform decisions regarding recoupling theory and practice in construction and engineering teaching and learning, but potentially also other fields.